Automotive industry as a factor of regional competitiveness in the Czech Republic - Rejka, Martin; Pělucha, Martin, 1980-; Květoň, Viktor, 1983-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
The automotive industry is one of the most important industries in the Czech Republic. This diploma thesis identifies its main characteristics and assesses its impact on regional competitiveness. The hypothesis tested in the practical section of this thesis is that suppliers producing high value-added products contribute to regional competitiveness more than suppliers of simple products. A review of relevant theories provides a sound reasoning to support this hypothesis. An analysis of available data from the Czech Republic, however, leads to a rejection of this hypothesis as the results from the practical part signalise that in the Czech Republic the impact of suppliers of simple products is higher than the impact of high value-added suppliers.
Vedoucí práce: Martin Pělucha
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: regionální studia [obor dipl. práce]; diplomové práce; master's theses